Truckxgaming / Mohamad Fakrul Hafiz Yahaya...[et al.] - Yahaya, Mohamad Fakrul Hafiz; Mohd Faisal, Mohamad Khairul Ikhwan; Ghazali, Mohammad Amirulakhyar; Saidin, Mohamad Khairul Hafiz; Izdad, Muhammad Irfan (2019)
Our business is TruckXGaming that started on 1st January 2021. TruckXGaming is about, we provide the gaming convenience for those people who want to play video games on the move. So, they do not need to waste their time and money to go to places that far away from their location just only for playing video games. It is because we will come to their places. We also accept offers for booking for any events at school, university and others. Our main headquarter is located at Taman Lagenda Indah,Sungai Petani, Kedah Darul Aman Our target market are those people who love playing video games regardless of adult or teenager or children. Our expectation on TruckXGaming in next five years are we will growing up and the number of gaming trucks and also branches will increase drastically. This is because the number of video gamers keep increasing day by day.